2022
DOI: 10.31083/j.jin2201005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Protects Against Cognition Deficits Caused by Sepsis-Associated Encephalopathy

Abstract: Background: One of the most serious complications of sepsis is sepsis-associated encephalopathy (SAE), which impairs the cognition ability of survivors. Environmental enrichment (EE) has been demonstrated to alleviate cognition deficits under many kinds of brain injury conditions. However, EE's effects on SAE remain unknown. Therefore, this study aimed to determine EE's effect on cognition disorders under SAE conditions and the underlying mechanism. Materials and Methods: Adult male rats, subject to SAE or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Consistent with this observation, we found that SD during late pregnancy resulted in oxidative stress and neuroinflammation in the hippocampus and prefrontal cortex in aged offspring, as evidenced by the increased levels of ROS and MDA, decreased SOD activity, and upregulation of the levels of Iba-1 and IL-1β, IL-6, and TNF-α. EE could improve cognitive impairment by inhibiting neuroinflammation and oxidative stress [ 39 ]. For example, an enriched environment was reported to improve middle cerebral artery occlusion-induced cognition impairment in Sprague–Dawley rats by suppressing neuroinflammation and oxidative stress and increasing the expression levels of synaptic plasticity-related proteins in the hippocampus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, we found that SD during late pregnancy resulted in oxidative stress and neuroinflammation in the hippocampus and prefrontal cortex in aged offspring, as evidenced by the increased levels of ROS and MDA, decreased SOD activity, and upregulation of the levels of Iba-1 and IL-1β, IL-6, and TNF-α. EE could improve cognitive impairment by inhibiting neuroinflammation and oxidative stress [ 39 ]. For example, an enriched environment was reported to improve middle cerebral artery occlusion-induced cognition impairment in Sprague–Dawley rats by suppressing neuroinflammation and oxidative stress and increasing the expression levels of synaptic plasticity-related proteins in the hippocampus [ 25 ].…”
Section: Discussionmentioning
confidence: 99%